Antimetastatic and antitumor activities of oncolytic NDV AMHA1 in a 3D culture model of breast cancer - Al-Shammari, Ahmed Majeed; Salman, Marwa Ibrahim (Frontiers in Molecular Biosciences, 2024)
Introduction Newcastle disease virus (NDV) AMHA1 is capable of killing cancer cells by direct replication or induction of apoptosis alongside other pathways. In this study, we report the potent antimetastatic and anticancer activities of NDV AMHA1 in a 3D spheroid model of breast cancer metastasis. Methods we used two breast cancer cell lines AMJ13 and MCF7 in our metastasis model system. Results First, we showed that NDV AMHA1 can infect and kill breast cancer cells in proliferating adherent cells and tumor spheroids using different virus doses and studying virus replication kinetics. We showed that NDV can infect and spread within the spheroids that represent metastasis before and after reattachment. Furthermore, we evaluated the ability of NDV to induce apoptosis in cancer spheroids and by virus tracking showed that NDV infection is essential for the elimination of these metastasis spheroids. Discussion The mechanism by which NDV induces cell killing in the metastasis model is the induction of caspase-3 and P21 and inhibition of Ki67 in cancer cells, but not in normal cells. In conclusion, these results indicate that NDV AMHA1 has the ability to kill breast cancer metastases in suspension or attached, and this is a novel finding of NDV AMHA1 being a possibly efficient therapy against human metastatic breast cancer.